High frequency stimulation activates hot spots of spontaneous synaptic transmission - Astacio, Herson; Bykhovskaia, Maria (Frontiers in Synaptic Neuroscience, 2025)
Neuronal transmitters are released at the morphological specializations known as active zones (AZs). Transmitters can be released either in response to a stimulus or spontaneously, and spontaneous transmission is a vital component of neuronal communication. Employing postsynaptically tethered calcium sensor GCaMP, we investigated how nerve stimulation affects spontaneous transmission at individual AZs at the Drosophila neuromuscular synapse. Optical monitoring of spontaneous transmission at individual AZs revealed that prolonged high-frequency stimulation (HFS, 30 Hz for 1 min) selectively activates the hot spots of spontaneous transmission, including the individual AZs with elevated activities as well as AZ clusters. In contrast, a brief tetanus (2 s) activated numerous low-activity AZs. We employed Monte-Carlo simulations of spontaneous transmission based on a three-state model of AZ preparedness, which incorporated longer-lasting (minutes) and shorter-lasting (sub-seconds to seconds) high-activity states of AZs. The simulations produced an accurate quantitative description of the variability and time-course of spontaneous transmission at individual AZs before and after the stimulation and suggested that HFS activates both longer-lasting and shorter-lasting states of AZ preparedness.